Győr How to compete with capital cities (Volume 7) - Tosics, Iván (European Investment Bank, 2019)
Located between three European capital cities, Győr has to work hard to attract investment and jobs. The Hungarian city has set itself up to attract innovative companies, creating new urban values such as education-based innovation, a high-quality urban environment and a lively cultural sphere. Here's how a "secondary city" builds on its industrial past even as it breaks away from its dependence on it.